AN ANALYSIS OF THE BANTU TRIAD:: UMBANDA, REINADO AND CANDOMBLÉ DE ANGOLA – AT THE CENTRO ESPÍRITA SÃO SEBASTIÃO (CESS) - Barcelos, Zuleica do Carmo Garcia de (Identidade!, 2022)
This article aims to analyze three Afro-Brazilian religious traditions – Umbanda, Reign and Candomblé of Angola – at Centro Espírita São Sebastião (CESS). Assuming that the geographic space used by the three manifestations is the same, the study will allow us to understand how they survive in the same sacred place, ensuring and demarcating their specific identities. Identities already legitimized by their historicity and their cultural traditions. Therefore, it was necessary to collect data through observation, in addition to information heard and recorded, as well as the support of theoretical researchers with a basis for writing. The research allowed, in the end, to understand how the legitimized identity is necessary to ensure the rites, the liturgy and the faith of its followers.